IMPACTOS AMBIENTAIS SOBRE OS AQUÍFEROS NA GRANDE MACEIÓ - AL. - CAVALCANTE, A.T.; BARROSO, C.M.R.; WANDERLEY, P.R.DE.M.; SANTOS, R.C. DE.A.L.; SANTOS, R.Q. (Águas Subterrâneas, 1994)
RESUMO NÃO DISPONÍVEL